1994
DOI: 10.1002/aja.1002000404
|View full text |Cite
|
Sign up to set email alerts
|

Type II collagen is transiently expressed during avian cardiac valve morphogenesis

Abstract: We present new evidence of the temporal and spatial expression of type I1 collagen in the embryonic chick heart during the very early stages of its development. In particular, we emphasize the distribution of its mRNA and protein during valve formation. Type I1 collagen as well as several other fibrillar collagens (types I, 111, and V) are present in stage 18 endocardial cushion mesenchymal cells. At stage 23, al(I1) collagen transcripts and the cognate polypeptide colocalize in the atrioventricular valves. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 64 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…Previous studies have suggested that the matrix of the cushion tissues may be of a transitional type, the composition of which is modified during morphogenesis and differentiation (Markwald et al, 1978;Bernanke and Orkin, 1984). A recent example of this is the loss of type II collagen from the cushion tissues and valves of the maturing embryonic chicken heart (Swiderski et al, 1994). MMP-2 was originally thought to be able to degrade only collagen types IV, V, and VII, fibronectin, and gelatin (Collier et al, 1988).…”
Section: Strongin Et Al 1995) the Expression Of Mt-mmp Wasmentioning
confidence: 99%
“…Previous studies have suggested that the matrix of the cushion tissues may be of a transitional type, the composition of which is modified during morphogenesis and differentiation (Markwald et al, 1978;Bernanke and Orkin, 1984). A recent example of this is the loss of type II collagen from the cushion tissues and valves of the maturing embryonic chicken heart (Swiderski et al, 1994). MMP-2 was originally thought to be able to degrade only collagen types IV, V, and VII, fibronectin, and gelatin (Collier et al, 1988).…”
Section: Strongin Et Al 1995) the Expression Of Mt-mmp Wasmentioning
confidence: 99%
“…Immunohistochemical studies demonstrate expression of many ECM components-including fibronectin, fibullin, laminin, NCAM, tenascin, and heparin sulfate proteoglycans-within the developing AV canal (for review, see Eisenberg and Markwald, 1995). Several collagens, including types I, II, III, IV, V, VIII, and XI, are also present in the embryonic heart (Hurle et al, 1994;Swiderski et al, 1994). We previously demonstrated that the type VI Grant sponsor: NIH SCOR Grant in Congenital Heart Disease (G.T.K.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the immunohistochemical technique for the detection of type II collagen relied on the fact that synthesis of type II collagen is considered cartilage-characteristic (Miller and Matukas, 1969;Miller, 1976;Kosher, 1983;Miyake, 1992,1995), even though type II collagen is also produced by a limited number of nonchondrogenic cell types (see Kosher, 1983, andSwiderski et al, 1994, for extensive reviews of the literature). The anti-SM␣-actin was utilized bearing in mind that in the chick and quail the use of this antibody was conclusive in deciding the nonmuscular nature of the neural-crest derived cells which are believed to be the precursors of the cardiac chondrocytes (López et al, 2000).…”
Section: Immunohistochemical Techniquesmentioning
confidence: 99%